Firm Size, Stock Price, Financial Leverage dan Income Smoothing di Era New Normal - Kusno, Hendra Sanjaya; Ramadhani, Novia Arthamelia Putri; Suriana, Ida (E-Jurnal Akuntansi; Vol 32 No 8 (2022), 2022)
This study aims to determine the effect of firm size, stock price and financial leverage on income smoothing. Hypothesis testing was carried out using multiple linear regression analysis. The research population uses Conventional Commercial Banks listed on the Indonesia Stock Exchange for the period 2020-2021. The sampling method used was purposive sampling, so the number of samples was 28 banks. This study provides empirical evidence that firm size has a positive effect on income smoothing; stock price has no effect on income smoothing; financial leverage has a negative effect on income smoothing. Keywords: Firm Size; Stock Price; Financial Leverage; Income Smoothing.